Sexual Violence Resulting From Sexually Nuanced Punitive Sanctions In The University Environment - Gatot, Diva Vania; Munir, Ahmad; Serbabagus, Shalahudin (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Sexual violence is a criminal act that leads to unilateral and unwanted sexual behavior, causing negative reactions in the victim. Sexual violence often occurs in the world of education, including in higher education. Higher education should be a safe environment for students, but cases of sexual violence that occur can actually cause trauma and depression in victims. This study aims to identify the elements of imposing sexual-nuanced punishments and forms of legal protection for victims of sexual violence in the higher education environment. Using a normative juridical method with a statutory and conceptual approach, this study utilizes primary and secondary legal materials. The results of the study indicate that imposing sexual- nuanced punishments requires special attention because of its sensitive and complex impacts. Based on Permendikbudristek Number 30 of 2021, various forms of sexual violence, including physical discrimination, gender identity harassment, and sexual threats, are strictly regulated. However, the limits of sexual-nuanced punishments have not been specifically explained. Legal protection for victims includes preventive and repressive efforts, such as education about sexual violence on campus and the imposition of prison sentences for perpetrators. This protection also includes emotional support and concrete assistance, such as guarantees of continuing education and employment and confidentiality of identity. The study suggests increasing awareness of sexual violence on campus, developing specific curricula, regular training, and further research to create a safe and inclusive academic environment.